2010
DOI: 10.1002/jbmr.238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous zoledronic acid plus subcutaneous teriparatide [rhPTH(1–34)] in postmenopausal osteoporosis

Abstract: Clinical data suggest concomitant therapy with bisphosphonates and parathyroid hormone (PTH) may blunt the anabolic effect of PTH; rodent models suggest that infrequently administered bisphosphonates may interact differently. To evaluate the effects of combination therapy with an intravenous infusion of zoledronic acid 5 mg and daily subcutaneous recombinant human (rh)PTH(1-34) (teriparatide) 20 mg versus either agent alone on bone mineral density (BMD) and bone turnover markers, we conducted a 1-year multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(188 citation statements)
references
References 45 publications
5
173
1
4
Order By: Relevance
“…As shown in Figure. 1A, of the 175 studies originally identified and screened, eight studies [3,12,[22][23][24][25][26][27] were included in the meta-analysis. Of those, two studies included patients with GIO, and the remaining six involved patients with PO (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure. 1A, of the 175 studies originally identified and screened, eight studies [3,12,[22][23][24][25][26][27] were included in the meta-analysis. Of those, two studies included patients with GIO, and the remaining six involved patients with PO (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The P values with these studies removed were borderline, indicating no obvious influence of any individual study on the pooled estimate. The heterogeneity observed may also be due to the different types of bisphosphonates used among the included studies (only Hadji et al [23] used risedronate and Cosman et al [25] used zoledronic acid), or selection bias or bias from intent-to-treat analysis in the three studies which evaluated vertebral fractures (McClung et al [24], Saag et al [3] and Body et al [27]). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed with different combinations of antiresorptive and anabolic drugs, to evaluate their potential additive, synergistic effects on bone metabolism, bone volume, and BMD. (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) Antiresorptives, depending on their potency, differentially influence the dynamic changes in bone formation and resorption that are induced by TPTD. In one study, raloxifene (RAL), when combined with TPTD, did not impair TPTD-induced stimulation of bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…With combination therapy, there was a rapid, but transient, reduction in CTX during the first 2 months, with a subsequent and gradual increase with levels remaining above baseline for last 6 months of the study. Levels of both markers were significantly lower with combination therapy versus teriparatide alone (p < 0.002) (41).…”
Section: Pthmentioning
confidence: 93%